Law Enforcement Dalam Mengawal Persaingan Dunia Usaha - Munawir Munawir (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2006)
This study aims to analyze the role of law enforcement in overseeing business competition to keep it healthy and fair. Uncontrolled business competition can lead to monopolies, cartels, and abuse of dominant positions that harm small businesses and consumers. This study uses a qualitative method with a literature study approach, examining regulations such as Law No. 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition and the role of the Business Competition Supervisory Commission (KPPU). The results show that the enforcement of business competition law still faces challenges, such as weak sanctions, lack of inter-agency coordination, and obstacles in proving cases. This study emphasizes that effective law enforcement in business competition requires strict regulations, tight supervision, and legal awareness among business actors in order to create a healthy and competitive business ecosystem.